Tanggung Jawab Hukum Apoteker terhadap Pemberian Obat Keras Tanpa Resep Dokter di Fasilitas Pelayanan Apotek - Tresnadi, Sony; Linda, Maura; Makbul, Ahmad (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Prescription drugs can only be obtained at certain health facilities, one of which is a pharmacy, where pharmacies, clinics, and hospitals provide two types of pharmaceutical services, namely the management of pharmaceutical supplies that include medical devices and disposable medical materials, and pharmaceutical services in clinical conditions. Prescription drugs can only be obtained at certain health facilities, one of which is a pharmacy, where the delivery can only be carried out by authorized health workers, namely pharmacists. Pharmacists at pharmacies can only dispense these prescription drugs based on a doctor's prescription. Based on Law Number 17 of 2023 concerning Health Article 320, there are two classifications of drugs, namely prescription drugs and non-prescription drugs. Prescription drugs are hard drugs, narcotics, and psychotropics, while nonprescription drugs are over-the-counter drugs and limited over-the-counter drugs. Prescription drugs are dispensed by pharmacists at pharmacy facilities. While nonprescription drugs can be obtained without requiring a prescription from a doctor. These non-prescription drugs can be obtained from pharmaceutical service facilities or other facilities permitted by laws and regulations such as hypermarkets, supermarkets, and minimarkets. The authority, rights, and obligations of pharmacists in carrying out their profession cover various aspects, from ethical responsibilities to compliance with applicable laws and regulations. Legal Regulations Based on the Health Law Health Law Number 17 of 2023 provides a clear regulatory framework regarding drug classification, including the role of pharmacists in distributing prescription drugs.